How to doodle the complete guide - Kamo (Tuttle Publishing, 2023)
In this guide, Kamo shows you how to draw the cutest sketches you've ever seen. And she makes drawing them so easy! Start with a squiggle, a circle or a line, then add a few strokes and voila -- your drawing is done! She includes hundreds of examples and shows you how to use them to decorate your sketchbook, journal, notebook, gift cards, school projects.